Estratégias socioeducativas das telenovelas em tempos de convergência: uma análise da narrativa de gênero e sexualidade na esfera ficcional de A Força do Querer - Ferreira, Flávio Júnior Freitas (2020)
The reconfigurations that have been updating the media over the years have caused adaptations in several media segments, such as television dramaturgy, which has in the soap opera its largest and most consumed product of serial fiction in Brazil. The general objective of this work is to understand how the socio-educational actions related to the gender transition of the character Ivana/Ivan that have taken place both in entertainment shows and news programs and in the official profiles of Rede Globo in digital social networks, from the fictional universe of A Força do Querer (The will power) (2017), by Glória Perez. The research considers the logic of the culture of participation that shapes forms of emission and reception in the era of convergence. For that, it proposes a qualitative, exploratory review, with bibliographic review, highlighting authors such as Henry Jenkins (2006; 2008), Yvana Fechine (2011; 2013; 2014), Maria Immacolata V. Lopes (2009; 2011; 2015; 2019) and researchers from Rede Obitel Brasil, the Brazilian branch of Obitel researchers (Ibero-American Observatory of Television Fiction), among others. When dealing with socio-educational actions in the television dramaturgy of A Força do Querer, both in traditional spaces as well as in on-line environments, we find that the media convergence has fostered a collaborative culture that is intertwined with the marketing strategies proposed by the broadcaster.